UPAYA MENINGKATKAN HASIL BELAJAR MATERI AKHLAK TERCELA MENGUNAKAN MEDIA POWER POINT INTERAKTIF BERBASIS VIDIO - Dessy Indriyani (JURNAL ILMIAH RESEARCH STUDENT, 2023)
The quality learning process involves many things, one of which is the strategy or learning method applied by the teacher. The learning strategy applied will greatly affect students in absorbing the material delivered by the teacher. The purpose of this study is to improve the ability of student learning outcomes by using video-based interactive power points on class VI moral creed material at MIS 01 Kepahiang.The results showed that, (1) the procedure for classroom action research in grade VI MIS 01 Kepahiang students consisted of 4 stages, namely planning, implementation, observation, and reflection, (2) the application of video-based interactive power point learning media could improve student learning outcomes in the moral creed subjects of grade VI MIS 01 Kepahiang students, (3) student learning outcomes improved from the start of cycle I, cycle II and cycle III. Student learning outcomes at the first cycle stage are 33,3%, then in the second cycle student learning outcomes are 66,6% and then increase again to 83,3% in cycle III.